The Lancet Global health (Elsevier, 2013)
"Research, commentary, correspondence, and blogs on the following subjects as they pertain to low- and middle-income countries: reproductive, maternal, neonatal, and child health; adolescent health; infectious diseases, including neglected tropical diseases; non-communicable diseases; the global health workforce; health systems; and health policy."--Title screen.
Keywords: Global Health; celosvětové zdraví; internacionalita; Public Health; Internationality; veřejné zdravotnictví